Locus of control, feeling of happiness and self-esteem: interrelation analysis (International Journal of Scientific Research and Management (IJSRM), 2017)
Recent interest in positive psychology is reflected in a plenty of studies conducted on its basic constructs in interrelation with personality features, social rules, business and technology development. It is recognized that the relationship between self-esteem, happiness, locus of control is complex: internal LOC is contributing to happiness, but it is not directly related to it; self-esteem is a powerful and important psychological factor in mental health and well-being; the feelings of being worthy and empowered are associated with significant achievements and high self-esteem; strong and appropriate self-esteem (when the discrepancy between “ideal” and “real” self is balanced) is correlated with more internal LOC (when the individual tends to believe that personal achievements depend on possessed features, vigor and persistence). Despite the special attention paid to happiness, locus of control and self-esteem, independently, theoretical and empirical equivocations within each literature foreclose many obvious predictions about the nature of their empirical distinction. In terms of theoretical framework, no model has achieved consensus as an ultimate theoretical background for any of the mentioned constructs. The purpose of this study is to investigate the mediating role of self-esteem, exploring the relationships between self-esteem and happiness, self-esteem and locus of control (LOC). It hypothesizes that self-esteem may be interpreted as a predictor of happiness and mediator in locus of control establishment. A plenty of various empirical studies results have been analysed in order to collect data for this theoretical study and some of the analysed results can be considered as arguable or incoherent